Enteropatbogenecity of E.coli from diarrhoeic ruminants in Himachal Pradesh* - Chachra, Deepti; Katoch, R C; Jasial, Sandeep; Mahajan, Arvind (The Indian Journal of Animal Sciences, 2012)
The study was designed to know the prevalence of K99 and F17 fimbrial antigens on 95 E.coli strains emanating from healthy and diarrhoeic calves, sheep and goats. The presence of K99 antigen alone was revealed. The presene of K99 in diarroheic animals such as calves was 20, sheep 14.29 and goats 40. The presence of F17 fimbrial antigen was recorded as 38.10 healthy calves, while 17.14, 14.29 and 4.0 in diarrhoeic calves, sheep and goats, respectively. The enteropathogenecity was conducted in rabbit ligated illial loop assay (RLILA) and mean dilation index was ascertained. The histopathomorphological alterations comprised haemorrhages and coagulative necrosis In liver, kidney, small intestine and heart muscles.